Evaluation of genetic markers for the analysis of THC levels of Cannabis sativa samples using principal component analysis – A preliminary study. (December 2022) - Cisana, S.; Omedei, M.; Di Nunzio, M.; Seganti, F.; Brenzini, V.; Coppi, A.; Berti, A.; Di Nunzio, C.; Garofano, P.; Alladio, E.
Abstract: Cannabis sativa is a worldwide commercial plant used for medicinal purposes, food and fiber production, and also as a recreational drug. Therefore, the identification and differentiation between legal and illegal C. sativa is of great importance for forensic investigations. In this study, principal component analysis (PCA), an exploratory data analysis technique, was tested to correlate the specific genotype with the concentration of tetrahydrocannabinol (THC) in the samples. C. sativa samples were obtained from legal growers in Piedmont, Italy, and from illegal drug seizures in the Turin region. DNA was extracted, quantified, amplified with a 13-loci multiplex STR and finally analyzed with an automated sequencer. The results showed a trend in the analyzed samples as they differed by their THC content and allele profiles. PCA yielded two clusters of samples that differed by specific allele profiles and THC concentrations. Further validation studies are needed, but this study could provide a new approach to forensic investigation and be a valuable aid to law enforcement in significant marijuana seizures or in tracing illicit drug trafficking routes.